Berliner Geowissenschaftlerinnen an der Friedrich-Wilhelms-Universität von 1906 bis 1945, eine Fallstudie - B. A. R. Mohr; A. Vogt (Fossil Record, 2003)
In dieser Untersuchung werden beispielhaft die Lebenswege und Karrieren von Berliner Geowissenschaftlerinnen im Zeitraum von 1906 bis 1945 nachgezeichnet und analysiert. Ähnlich wie an anderen deutschen bzw. westlichen Universitäten, aber im Gegensatz zu Russland, begann die Tätigkeit von Frauen in den Geowissenschaften spät, und das Fach wurde auch relativ selten gewählt, hauptsächlich wegen der zu geringen Berufschancen. Aber die besondere Situation in Berlin mit mehreren sich ergänzenden Institutionen und dem daraus resultierenden breiten Spektrum an geowissenschaftlichen Disziplinen, sowie ausgezeichneten Professoren, ließ dennoch Raum für eine Ausbildung in diesem Bereich und erlaubte, wenn auch in bescheidenem Maße, eine gewisse Karrieremöglichkeit.Während der hier untersuchten 40 Jahre haben weniger als 20 Frauen in den Geowissenschaften und benachbarten Gebieten promoviert. Mehrere dieser Frauen blieben in dem von ihnen gewählten Fach weiterhin aktiv und wurden erfolgreich. Zwei Frauen gelang eine akademische Karriere — eine als Universitätsprofessorin, die auch Schülerinnen hatte. Andere arbeiteten an staatlichen Institutionen, wie z. B. dem Geologischen Landesamt. Wenige Frauen blieben nach ihrer Verheiratung beruflich aktiv, wenn auch nicht offiziell angestellt, sondern als Ehefrauen. Andere arbeiteten als "Ersatz" für die im Kriege stehenden Männer. Einige waren aus persönlichen und politischen Gründen, insbesondere während der NS-Zeit, gezwungen, die Geowissenschaften zu verlassen, konnten aber teilweise auf anderen Gebieten erfolgreich arbeiten.This paper documents the lives and careers of women geoscientists at the Berlin Friedrich-Wilhelms-University from 1906 through 1945. Traditionally, in Germany, women had difficulties to be accepted in geosciences (except for geography/geology teachers), because of strong links between geology and mining, a field dominated clearly by men. In western European countries, as well as in the U.S.A. and Australia, the situation was similar in that women started late and in small numbers to study geology. This was, however, in contrast to Russia and later the Soviet Union where women were relatively early accepted even as university teachers.The data for this paper were gathered from Berlin University institutions, such as the historical archive and the library of the Palaeontological Institute, and in addition personal contacts were used. Women who had studied either geography, geology/palaeontology, geophysics, mineralogy or botany/palaeobotany are subject of this study. Only those are considered who had strong affiliations to geosciences proper, in all 17 women.During the first half of the 20th century the Berlin Friedrich-Wilhelms-University, founded in 1810, was one of the most important institutions concerning higher education in Germany, especially for women. The official opening of this university for women students was in 1908, somewhat later than at other German universities. Once admitted, however, the number of dissertations completed by women was relatively high, and, 30% of all habilitations (advanced degree which allows teaching at universities) in Germany and 50% of all habilitations in the natural sciences were accomplished at Berlin between 1918/19 to 1932.The geosciences were, together with medicine, chemistry, physics, botany and zoology, very strong scientifical and in teaching. Geoscientists of international reputation worked at large institutions, affiliated or being part of the University, such as the Prussian (later German) Geological Survey, the Institute of Geology and Palaeontology at the Museum of Natural History or the Institute and Museum of Oceanography, and were the advisers and reviewers of women Diploma and PhD students.doi:10.1002/mmng.20030060103